MISSING MENSTRUATORS: HOW ACTIVIST WORK HIGHLIGHTS A KNOWLEDGE GAP - Sakač Hadžić, Marina (Pravni zapisi, 2025)
With the global and cultural shifts challenging the silence and taboo, menstruation is becoming increasingly present in the media. By looking the work of artists and activists, this paper highlights the development of knowledge about menstruation. In promoting menstruation and period poverty, activists and NGOs have contributed to changes in schools and universities in Serbia and the Western Balkans. Some of these institutions now provide free menstrual products. The paper explores the role of digital activists and civil society as drivers of change, focusing on producing and sharing knowledge about menstruating bodies. They fill gaps created by the neglect or lack of interest of public health institutions. This draws on legal reforms, civil society contributions, critical menstrual studies, digital ethnography, and content analysis.
Keywords: Digital Activism; Menstrual Activism; Knowledge Production; Human Rights; Public Health Law; Serbia; Western Balkans